Thermal annealing effects on the structural and electrical properties of SiC nanoparticles prepared by pulsed laser ablation in water - Esmael, M. M.; Omar, M. S.; Dagdelen, F. (Iop Publishing Ltd, 2026)
Silicon carbide (SiC) nanoparticles were synthesised by pulsed laser ablation in water and subsequently thermally annealed at 300-570 K. Field-emission scanning electron microscopy revealed that the as-prepared nanoparticles were uniformly dispersed, with an average particle size of approximately 17.19 nm. After annealing at 570 K, partial coalescence and significant grain growth (similar to 163 nm) were observed, indicating thermally driven diffusion, sintering, and enhanced structural ordering. X-ray diffraction analysis showed that the as-prepared SiC nanoparticles were predominantly amorphous, with no distinct crystalline peaks. After two thermal annealing cycles up to 570 K, diffraction peaks corresponding to the 6H-SiC phase emerged, accompanied by peak sharpening and slight shifts, suggesting improved crystallinity, grain coalescence, and partial stress relaxation. Hall-effect measurements of SiC thin films fabricated from the nanoparticles revealed thermally activated electrical behaviour between 300 K and 570 K. The electrical conductivity remained nearly constant at low temperatures and increased above 480 K due to the excitation of charge carriers. A reduction in conductivity during the second heating cycle was attributed to defect trapping and partial oxidation. Carrier mobility decreased with increasing temperature in both cycles, consistent with phonon scattering, and was lower during the second cycle due to enhanced defect and surface scattering.
Keywords: SiC; nanoparticles; hall effect; annealing; laser ablation; aqueous synthesis